Mutation of the Inducible ARABIDOPSIS THALIANA CYTOCHROME P450 REDUCTASE2 Alters Lignin Composition and Improves Saccharification - Sundin, Lisa (Plant Physiol, 2014)
ARABIDOPSIS THALIANA CYTOCHROME P450 REDUCTASE1 (ATR1) and ATR2 provide electrons from NADPH to a large number of CYTOCHROME P450 (CYP450) enzymes in Arabidopsis (Arabidopsis thaliana). Whereas ATR1 is constitutively expressed, the expression of ATR2 appears to be induced during lignin biosynthesis and upon stresses. Therefore, ATR2 was hypothesized to be preferentially involved in providing electrons to the three CYP450s involved in lignin biosynthesis: CINNAMATE 4-HYDROXYLASE (C4H), p-COUMARATE 3-HYDROXYLASE1 (C3H1), and FERULATE 5-HYDROXYLASE1 (F5H1). Here, we show that the atr2 mutation resulted in a 6% reduction in total lignin amount in the main inflorescence stem and a compositional shift of the remaining lignin to a 10-fold higher fraction of p-hydroxyphenyl units at the expense of syringyl units. Phenolic profiling revealed shifts in lignin-related phenolic metabolites, in particular with the substrates of C4H, C3H1 and F5H1 accumulating in atr2 mutants. Glucosinolate and flavonol glycoside biosynthesis, both of which also rely on CYP450 activities, appeared less affected. The cellulose in the atr2 inflorescence stems was more susceptible to enzymatic hydrolysis after alkaline pretreatment, making ATR2 a potential target for engineering plant cell walls for biofuel production.